ANALISIS PENGGUNAAN SISTEM E-KINERJA GURU DI SMK NEGERI 3 GOWA - Khairunnisa, Khairunnisa; Syamsu Kamaruddin; Sumarlin Mus (Nusantara Hasana Journal, 2025)
Digital transformation in the education sector has become a necessity in the modern era, especially in supporting the improvement of performance and accountability of educators through the application of information technology. The e-Performance system is present as an important innovation to record, monitor, and evaluate teacher performance more objectively, transparently, and in real-time, but its implementation still faces various challenges in various regions, including in the Vocational High School (SMK) environment which has a higher complexity of tasks compared to public schools. This study aims to identify and analyze the process of using the e-Performance system by teachers at SMKN 3 Gowa, with a focus on teachers' understanding of the system, filling in Employee Performance Targets (SKP) electronically, and implementing digital-based monitoring and evaluation. This study used a qualitative approach with a descriptive research type, which allowed researchers to explore experiences, perceptions, and dynamics that occur in field practice in depth, through data collection techniques such as in-depth interviews, observations, and documentation involving the principal, vice principal for curriculum, and teachers as key informants. The results of the study showed significant variations in the level of teacher understanding of the e-Performance system, where some teachers, especially younger ones, were able to operate the application relatively smoothly, while others, especially older teachers or those with low digital literacy, experienced difficulties in accessing and utilizing important features in the system. Filling out the SKP electronically was identified as a fairly complex process, with many teachers admitting confusion in setting performance targets according to indicators and experiencing technical obstacles that impacted the validity of the input data. In addition, monitoring and evaluation of teacher performance through the e-Performance system at SMKN 3 Gowa has not been optimally utilized due to limited time for school management, technical obstacles such as unstable internet connections, and a low digital data-based work culture within the school environment. These findings confirm that although the e-Performance system has been implemented, its effectiveness in supporting teacher performance management still requires more structured interventions, both in terms of improving teachers' digital competencies, refining the system's technical features, and formulating evidence-based monitoring policies. The contribution of this research lies in enriching the literature related to the implementation of technology-based performance management in vocational schools, especially in the relatively underexplored Eastern Indonesia region, as well as providing practical recommendations for policymakers and schools in formulating strategies to optimize the e-Performance system so that it truly functions as an instrument for improving professionalism and the quality of educational services.